The Influence of Brand Image, Product Quality, and Customer Service on Purchase Decision at Current Jaya Store in Madiun City - Hogas, Reynal Kusuma; Aziz, Noor; Sudiyono, Widhiyo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The purpose of this study is to ascertain whether Lancar Jaya Stores customers in Madiun City made a purchase of PVC ceiling based on brand image, product quality, and service quality. This study employs a quantitative approach to research. in studies employing multiple linear regression methods. Utilizing the Purposive Sampling method for sampling. There were 96 respondents in the sample. It is demonstrated by statistical tests that product quality has a positive and significant impact on decisions about what to buy, service quality has a positive and significant impact on decisions about what to buy, and the image of the brand”has a partial effect on purchasing decisions .. Purchasing decisions are influenced simultaneously.